Penerapan Metode SAW Pada Penentuan Penerima Beasiswa Lazizmu - Ike Yunia Pasa; Nur Wachid Adi Prasetya; Ratih Hafsarah Maharrani (Universitas Muhammadiyah Purworejo, 2022)
Scholarships are awards in the form of financial aid to individuals or organizations for their work performance. Purworejo Muhammadiyah University (UMP) as an educational institution, also provides scholarships to its students. One of them is the Lazizmu scholarship. In the process, the campus needs to prioritize students according to their criteria. However, the accuracy of student selection is still low; therefore it is necessary to implement an efficient method to assist the selection process for the acceptance of the Lazizmu scholarship at UMP. This research aims to apply the calculation of the Simple Additive Weighting (SAW) method to the selection problem of the Lazizmu scholarship recipient, by conducting a test using a confusion matrix. The results of the confusion matrix test show that the level of accuracy in calculations using the Simple Additive Weighting (SAW) method is 80%, thus it can be developed into a decision support system to determine the acceptance of the Lazizmu scholarship at the Muhammadiyah University of Purworejo (UMP).